2022
DOI: 10.1136/rmdopen-2022-002290
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of remote care interventions: a systematic review informing the 2022 EULAR Points to Consider for remote care in rheumatic and musculoskeletal diseases

Abstract: ObjectiveTo perform a systematic literature review (SLR) on different outcomes of remote care compared with face-to-face (F2F) care, its implementation into clinical practice and to identify drivers and barriers in order to inform a task force formulating the EULAR Points to Consider for remote care in rheumatic and musculoskeletal diseases (RMDs).MethodsA search strategy was developed and run in Medline (PubMed), Embase and Cochrane Library. Two reviewers independently performed standardised data extraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…Compared to videoconferencing, more research has focused on telephonedelivered interventions for people with knee OA [13•, 14, 15••, 16, 17,35]. Numerous RCTs have shown that telephone-delivered exercise can benefit people with knee OA.…”
Section: Telephone Consultationsmentioning
confidence: 99%
“…Compared to videoconferencing, more research has focused on telephonedelivered interventions for people with knee OA [13•, 14, 15••, 16, 17,35]. Numerous RCTs have shown that telephone-delivered exercise can benefit people with knee OA.…”
Section: Telephone Consultationsmentioning
confidence: 99%
“…Results from a recent EULAR guideline on remote care show 10,11 that the vast majority of studies have been conducted within non-inflammatory RMDs, with osteoarthritis (OA) being the disease where most telehealth interventions have been developed. Within inflammatory RMDs, most interventions have been developed for patients with rheumatoid arthritis (RA).…”
Section: Current Evidencementioning
confidence: 99%
“…We have recently published guidance on the use of telemedicine in rheumatology (7). During the systemic literature review for that topic, we did not find any polymyalgia rheumatica specific study (8). Telemedicine would certainly facilitate pre-diagnostic processes and in some instances ruling out a diagnosis of polymyalgia rheumatica, but a diagnosis should always be established in a face-toface visit after clinical examination (7).…”
mentioning
confidence: 95%